High pressure bioscience and biotechnology: proceedings of the International Conference on High Pressure Bioscience and Biotechnology, Kyoto, Japan, November 5-9, 1995 - Hayashi, Rikimaru; Balny, Claude (Elsevier, 1996)
For many years, pressure was disregarded by biochemists. Today, there is a growing interest in pressure as a variable acting on biosystems. The activities that are currently of interest to scientists working in the field of High Pressure Bioscience and Biotechnology have been well presented in this volume, with topics ranging from physical biochemistry, microbiology, molecular biology and food science to industrial application. The editors have been successful in promoting the possibility of applying pressure in specific biotechnological areas, not only for food processing but also for biotechnology in general. These proceedings present an up-to-date view of high pressure research and will contribute to future developments in this field
Includes bibliographical references and indexes. - Print version record
Keywords: Electronic books; Congress; Electronic books -- Conference papers and proceedings; Konferenzschrift